[math]\cos(-x)=\cos(x)[/math]
[math]\sin(-x)=\-sin(x)[/math]
[math]\cos(\pi+x)=-\cos(x)[/math]
[math]\sin(\pi+x)=-\sin(x)[/math]
[math]\cos(\pi-x)=-\cos(x)[/math]
[math]\sin(\pi+x)=sin(x)[/math]
[math]\cos\left(\frac{\pi}{2}+x\right)=-\sin(x)[/math]
[math]\sin\left(\frac{\pi}{2}+x\right)=\cos(x)[/math]
[math]\cos\left(\frac{\pi}{2}-x\right)=\sin(x)[/math]
[math]\sin\left(\frac{\pi}{2}-x\right)=\cos(x)[/math]
[math]\cos\left(\frac{3\pi}{2}+x \right)=\sin(x)[/math]
[math]\sin\left(\frac{3\pi}{2}+x\right)=-\cos(x)[/math]
[math]\cos\left(\frac{3\pi}{2}-x\right)=-\sin(x)[/math]
[math]\sin\left(\frac{3\pi}{2}-x\right)=-\cos(x)[/math]